Het 50/25 : Hedendaagse Kunst in de Leuvense Binnenstad. - Cosemans, Anneleen; Mariëns, Isabelle; Quireyns, Alan; Vereertbrugghen, Pieter; Verschueren, Sofie; Exhibition. 50/25 : Hedendaagse Kunst in de Leuvense binnenstad. Leuven. Project3000 Leuven. 2007-08-31. 2007-08-05 (Leuven : Cypres Galerie Leuven Project3000 Leuven, 2007)
Baeyens, Nicolas ; Brantt ; Claikens, Stijn ; Corluy, Eva ; Dean, Jamez ; Devillé, Joachim ; Dhondt, Lara ; Dries, Tom ; Enoki, Yoko ; Foulon, Jo ; Hamers, Karolien ; Heeren, Pascal ; Jaber, Athar ; Kenisman ; Lauwaert, Tessa ; De Meyer, Peter ; de Moortel, Joris Van ; Spincemaille, Ief ; Van Steerteghem, Evelien ; Van Stichel, Niko ; Tas, Nele ; Vaes, Niels ; Verbeckmoes, Kenny ; Vercruysse, Emilie ; Verschueren, Bart ; Vervoort, Mick ; Wlodkowski, Julia ; Woestenberghs, Tom
Nederlands
boek
Keywords: Leuven